Bolstering functionality in multilayer and bilayer WS₂ via focused laser micro-engraving - Chan, Si Min (2023)
Laser thinning of multilayer transition metal dichalcogenide (TMD) crystals has long been explored for its potential to produce localized domains of optically functional monolayers. Despite the high spatial control and resolution of the laser, the range of appropriate applications for these laser-thinned domains is still limited by the peripheral regions of unaltered thick multilayers. Herein, we report a newfound property of the laser-thinned regions to adhere strongly to the underlying substrate when lasered down to the monolayer limit. Upon a brief sonication in various solvents, the surrounding pristine multilayers can be lifted off, solely leaving behind the post-lasered monolayer patterns. Coupled with the flexible maneuver of the laser, various monolayer designs can be achieved, including micro-antenna, waveguide, and electrode geometries with lateral line widths at 1.5 µm resolution. Furthermore, we also detail the optical properties of the monolayers obtained from laser thinning, with those acquired from multilayers containing more defect-bound excitons, whereas those lasered from bilayers presenting a trion-dominated profile similar to as-grown monolayers. Together, these findings allow for faster and more efficient multilayer removal and areal shaping of optically active monolayer domains, in comparison to multistep and complex standard lithographic etching (lithography–etch–develop) procedures.